Volume and flow modulation strategies to mitigate post-hepatectomy liver failure - Bell, Richard; Begum, Saleema; Prasad, Raj; Taura, Kojiro; Dasari, Bobby V. M. (Frontiers in Oncology, 2022)
Introduction Post hepatectomy liver failure is the most common cause of death following major hepatic resections with a perioperative mortality rate between 40% to 60%. Various strategies have been devised to increase the volume and function of future liver remnant (FLR). This study aims to review the strategies used for volume and flow modulation to reduce the incidence of post hepatectomy liver failure. Method An electronic search was performed of the MEDLINE, EMBASE and PubMed databases from 2000 to 2022 using the following search strategy “Post hepatectomy liver failure”, “flow modulation”, “small for size flow syndrome”, “portal vein embolization”, “dual vein embolization”, “ALPPS” and “staged hepatectomy” to identify all articles published relating to this topic. Results Volume and flow modulation strategies have evolved over time to maximize the volume and function of FLR to mitigate the risk of PHLF. Portal vein with or without hepatic vein embolization/ligation, ALPPS, and staged hepatectomy have resulted in significant hypertrophy and kinetic growth of FLR. Similarly, techniques including portal flow diversion, splenic artery ligation, splenectomy and pharmacological agents like somatostatin and terlipressin are employed to reduce the risk of small for size flow syndrome SFSF syndrome by decreasing portal venous flow and increasing hepatic artery flow at the same time. Conclusion The current review outlines the various strategies of volume and flow modulation that can be used in isolation or combination in the management of patients at risk of PHLF.